El mito Habsbúrgico en la obra de Joseph Roth - Vázquez Larrea, Iñaki (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The current article explores the logic and the political function of the Habsburgic myth in Joseph´s Roth Literary work, following Raymond´s Williams marxist theory of a an autonomous ideological feeling structure that must be analyze out of the author’s literary